Evaluation of Milking Facilities and Machinery in Dairy Operations of Central Anatolia - Cevdet Sağlam; Zeynel Abidin Kuş; Serkan Yılmaz (Turkish Journal of Agriculture: Food Science and Technology)
The present study was conducted to investigate the recent changes in dairy operations of Central Anatolia and to evaluate the milking facilities and machinery capacities of the facilities.The basic objective is to put forward the recent changes through the state supports provided to dairy facilities of the Central Anatolian Provinces. While investigating and evaluating the recent changes, milking parlors, milking machinery and livestock inventories of the facilities were taken into consideration. The relevant data were gathered from the recent records of Turkish Institute of Statistics (TUIK), Agriculture and Rural Development Support Institution (TKDK) and the Ministry of Economy.As a result, in this study while in determining the recent changes in dairy facilities of the Central Anatolian Provinces, the number of milking machinery, milking parlors and livestock inventories were taken into consideration as well as milk yields per animal and number of animals per machine. According to TUIK records for last six years; 384 milking parlors were built, 8877 milking machinery were bought, the increment in the number of livestock inventories and milk yields per animal were taken place as 62.9% and 9.5% respectively. It is thought that supports provided to dairy operations had a great effect on the recent developments. Such supports should also be provided in the future to furnish entire dairy operations with modern machinery and equipment, thus to improve yields and product qualities.